2018
DOI: 10.1007/s00784-018-2453-7
|View full text |Cite
|
Sign up to set email alerts
|

Properties of calcium silicate-monobasic calcium phosphate materials for endodontics containing tantalum pentoxide and zirconium oxide

Abstract: The ability to nucleate apatite may lead many clinical advantages: In orthograde endodontics, it may improve the sealing ability by the deposition of CaPs at the material-root dentine interface, and in endodontic surgery, it could promote bone and periodontal tissue regeneration. As premixed materials, their application in endodontics may result easier in several complex endodontic situations (apicoectomy, root perforation, presence of wide/wet apices).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 52 publications
3
88
2
5
Order By: Relevance
“…The alkalizing activity of ESRRM putty, showing a pH > 11:7 after 1-day immersion, also supports a previous finding by Candeiro et al [40]. Moreover, ESRRM putty showed a higher alkalizing activity in the long term: pH mean value at 28-day evaluation was 11, which is consistent with another study by Zamparini et al [41]. On the other hand, a study done by Lee et al [42] found a lower pH of ESRRM putty at 24 hours, with the maximum level reached at 7 days and without maintenance of a high pH at 14 days.…”
Section: Discussionsupporting
confidence: 91%
“…The alkalizing activity of ESRRM putty, showing a pH > 11:7 after 1-day immersion, also supports a previous finding by Candeiro et al [40]. Moreover, ESRRM putty showed a higher alkalizing activity in the long term: pH mean value at 28-day evaluation was 11, which is consistent with another study by Zamparini et al [41]. On the other hand, a study done by Lee et al [42] found a lower pH of ESRRM putty at 24 hours, with the maximum level reached at 7 days and without maintenance of a high pH at 14 days.…”
Section: Discussionsupporting
confidence: 91%
“…Premixed, ready‐to‐use calcium silicate‐based endodontic sealers, such as EndoSequence (Brasseler, Savannah, GA, USA) and TotalFill BC Sealer (FKG Dentaire, La Chaux‐de‐Fonds, Switzerland), have been studied (Zamparini et al . ). TotalFill BC has adequate physicochemical properties, but appears to be soluble (Poggio et al .…”
Section: Introductionmentioning
confidence: 97%
“…Root canal sealers based on calcium silicates Correspondence: M ario Tanomaru Filho, Department of Restorative Dentistry, Araraquara Dental School, São Paulo State University-UNESP, Rua Humait a, 1680, PO 331,Araraquara,SP, were developed as materials that offer biocompatibility, bioactivity and nongenotoxicity . Premixed, ready-to-use calcium silicatebased endodontic sealers, such as EndoSequence (Brasseler, Savannah, GA, USA) and TotalFill BC Sealer (FKG Dentaire, La Chaux-de-Fonds, Switzerland), have been studied (Zamparini et al 2019). TotalFill BC has adequate physicochemical properties, but appears to be soluble (Poggio et al 2017, Tanomaru-Filho et al 2017, Colombo et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental 3D scaffolds allow the expression of angiogenic markers by VW-MSCs after 72 h of culture. Further studies, with longer growth kinetics, are needed to investigate the differentiated fate of these cells grown on the experimental 3D culture systems containing CaSi and calcium phosphate for pulp and bone regeneration [56].…”
Section: Discussionmentioning
confidence: 99%